PENERAPAN CUSTOMER DUE DILIGENCE PADA SHOPEEPAYLATER SEBAGAI ALTERNATIF METODE PEMBAYARAN: Application of Customer Due Diligence on ShopeePayLater as an Alternative Payment Method - Rozaq, Hendrianto; Santoso, Rahmat (AMICUS CURIAE, 2025)
The existence of financial technology (Fintech) in Peer to Peer Lending (P2P Lending) services with the PayLater scheme is the public's choice for payment transactions in the Shopee application (in collaboration with PT. CF). ShopeePayLater (SPayLater) is a trend today because of its simplicity of activation and use, especially for young people, who tend to choose it over bank credit. However, the lack of selectivity in carrying out Customer Due Diligence on prospective debtor customers can lead to an increase in credit arrears or bad credit which results in default. This relates to the principle of prudence in PT CF's credit policy as a provider of SPayLater. Researchers are interested in researching and making the focus of this research by raising the issue of how is the application of Customer Due Diligence on ShopeePayLater as an alternative payment method? The conclusion of this research is that there is no strict supervision and mechanism for prospective debtor customers, so that Customer Due Diligence does not run according to applicable regulations.